Differential Regulation of Synaptic Vesicle Tethering and Docking by UNC-18 and TOM-1 - Gracheva, Elena O.; Maryon, Ed B.; Berthelot, Martine; Richmond, Janet E. (Frontiers in Synaptic Neuroscience, 2010)
The assembly of SNARE complexes between syntaxin, SNAP-25 and synaptobrevin is required to prime synaptic vesicles for fusion. Since Munc18 and tomosyn compete for syntaxin interactions, the interplay between these proteins is predicted to be important in regulating synaptic transmission. We explored this possibility, by examining genetic interactions between C. elegans unc-18(Munc18), unc-64(syntaxin) and tom-1(tomosyn). We have previously demonstrated that unc-18 mutants have reduced synaptic transmission, whereas tom-1 mutants exhibit enhanced release. Here we show that the unc-18 mutant release defect is associated with loss of two morphologically distinct vesicle pools; those tethered within 25 nm of the plasma membrane and those docked with the plasma membrane. In contrast, priming defective unc-13 mutants accumulate tethered vesicles, while docked vesicles are greatly reduced, indicating tethering is UNC-18-dependent and occurs in the absence of priming. C. elegans unc-64 mutants phenocopy unc-18 mutants, losing both tethered and docked vesicles, whereas overexpression of open syntaxin preferentially increases vesicle docking, suggesting UNC-18/closed syntaxin interactions are responsible for vesicle tethering. Given the competition between vertebrate tomosyn and Munc18, for syntaxin binding, we hypothesized that C. elegans TOM-1 may inhibit both UNC-18-dependent vesicle targeting steps. Consistent with this hypothesis, tom-1 mutants exhibit enhanced UNC-18 plasma membrane localization and a concomitant increase in both tethered and docked synaptic vesicles. Furthermore, in tom-1;unc-18 double mutants the docked, primed vesicle pool is preferentially rescued relative to unc-18 single mutants. Together these data provide evidence for the differential regulation of two vesicle targeting steps by UNC-18 and TOM-1 through competitive interactions with syntaxin.